Alcohol and motorcycle fatalities. - Baker, S P (1977)
A series of 99 fatal motorcycle crashes in Maryland was studied retrospectively, using police and medical examiner records. Blood alcohol concentrations were determined for 62 motorcycle drivers; measurable amounts of alcohol were found in two-thirds (41), and one-half (31) had illegally high concentrations of 100 mg/100 ml or more. The police report mentioned alcohol in only 9 instances. High blood alcohol concentrations were found most commonly among drivers age 20-34.